2019
DOI: 10.33794/qjas.vol9.iss2.91
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Assessing Fusarium Damage to Wheat Kernels

Abstract: Fusarium Head Blight (FHB), or head scab, primarily caused by Fusarium graminearum Schw., is a destructive disease of wheat (Triticum aestivum L.). It has reemerged worldwide as a disease of economic importance. Damage produced by the fungus includes: reduction of yield, mycotoxin contamination (DON), discolored, shriveled “tombstone” kernels and reduction in seed quality. The disease also reduces the test weight and lowers the market grade. Thus, there is great interest among breeders in selecting for resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…F-measure was used to balance Precision and Recall [30]. These metrics were calculated as follows: (10) where TP represents the pixel area correctly predicted as wheat ear; TN represents the pixel area correctly predicted as background; FP is the pixel area predicted as wheat ear, but actually these pixels belong to the background. FN is the pixel area predicted as background, but actually these pixels belong to wheat ears.…”
Section: ) Rate Of Diseased Wheat Earsmentioning
confidence: 99%
“…F-measure was used to balance Precision and Recall [30]. These metrics were calculated as follows: (10) where TP represents the pixel area correctly predicted as wheat ear; TN represents the pixel area correctly predicted as background; FP is the pixel area predicted as wheat ear, but actually these pixels belong to the background. FN is the pixel area predicted as background, but actually these pixels belong to wheat ears.…”
Section: ) Rate Of Diseased Wheat Earsmentioning
confidence: 99%
“…Type I and Type II resistances can be assessed by a visual evaluation in the field, which provides advantages in terms of ease and quickness compared with other resistance measurements. While incidence and severity have been effective criteria for evaluating FHB resistance, Khaeim et al (2019) points out limitations of using field ratings to evaluate Type I and II resistance: (1) incidence and severity do not always reliably correlate with accumulated toxin levels; (2) optimum timing for rating varies by genotype and environmental conditions; (3) accurate rating requires a random sample, but this is difficult to accomplish or verify in the field; and (4) ratings are likely to differ between personnel if not all done by one individual [11].…”
Section: Introductionmentioning
confidence: 99%
“…FDK is quantified traditionally by estimating the amount of visibly damaged kernels, which appear smaller, shriveled, and in a range of colors from pale pink to brown ( Delwiche et al., 2010 ), according to a predetermined scale for visual assessments or by employing manual tools ( Ackerman et al., 2022 ). Comparisons between both types of resistance (resistance types II and III) have revealed that it would be more efficient and consistent to estimate FHB than the degree of colonization on the spike ( Agostinelli, 2009 ; Balut et al., 2013 ; Khaeim et al., 2019 ; Ackerman et al., 2022 ). However, screening by either manual or visual assessments is a labor- and time-consuming process for rating genotypes, is biased due to the subjectivity of visual assessments, and has low reproducibility among experiments ( Barbedo et al., 2015 ; Khaeim et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%